1986
DOI: 10.1002/1097-0142(19860701)58:1<22::aid-cncr2820580106>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative radiotherapy in Dukes' B and C carcinoma of the rectum and rectosigmoid: A randomized multicenter study

Abstract: Results obtained during the first 5 years of a randomized study of postoperative radiotherapy (50 Gy) are presented. Criteria for randomization were fulfilled in 494 of 861 patients with Dukes' B and C tumors, when the trial was closed. Severe complications from radiotherapy approximated 10%. Probability of survival without local failure within 24 months was significantly higher after radiotherapy in patients with Dukes' C tumors, and the time of local failure was delayed 1 year. Patients with Dukes' B tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
53
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(57 citation statements)
references
References 14 publications
3
53
0
1
Order By: Relevance
“…Exclusion criteria were: tumour above the pelvis, patient aged >80 years, non-radical surgery, bedridden more than 50% of day 20-25 days after surgery, post-operative complications, previous cancer within 5 years and previous radiotherapy. A detailed description of material and methods has been published in Balslev et al (1982Balslev et al ( , 1986). In the group of patients randomized to receive radiotherapy 92% actually received treatment, and 84% were treated to the prescribed target dose.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exclusion criteria were: tumour above the pelvis, patient aged >80 years, non-radical surgery, bedridden more than 50% of day 20-25 days after surgery, post-operative complications, previous cancer within 5 years and previous radiotherapy. A detailed description of material and methods has been published in Balslev et al (1982Balslev et al ( , 1986). In the group of patients randomized to receive radiotherapy 92% actually received treatment, and 84% were treated to the prescribed target dose.…”
Section: Methodsmentioning
confidence: 99%
“…The Danish Cooperative Group on Colorectal Cancer (CRES) conducted a prospective, randomized trial to elucidate whether the deleterious effects of post-operative radiotherapy were justified by an improved survival and/or a delay in the first recurrence (Balslev et al, 1982(Balslev et al, , 1986 bowel wall completely, and C tumours as having metastasized to the regional lymph nodes regardless of the degree of bowel wall penetration. No subdivision of Dukes' stages was used.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Nevertheless, the incidence of local recurrence remains high (10 -30%). [5][6][7][8][9][10] Moderate-to high-dose neoadjuvant preoperative radiotherapy has been shown to induce tumor regression and downstaging, thus significantly improving local control. 7,10 -18 The role of preoperative radiotherapy in survival remains controversial, with some studies reporting a minimal effect, 17,19,20 whereas in other trials a significant impact has been shown.…”
mentioning
confidence: 99%
“…Danimarka çalışmasında tek başına cerrahi kolundaki lokal nüks oranı dikkat çekici düşüklüktedir. [10] Çalışma dizaynı ve hasta seçiminin düzgün yapıldığı, RT doz ve tekniklerinin homojen olduğu gruplarda yapılan çalışmalarda anlamlı istatiksel fark bulunmuştur. [9,11] "National Surgical Adjuvant Bowel and Breast Project" (NSABP)-R01 en fazla sayıda hastayı içe-ren, tamamlanması neredeyse bir dekat süren bir çalışmadır.…”
Section: Ameliyat Sonrası Radyoterapiunclassified